Taking charge of adult ADHD - Barkley, Russell A., 1949- (New York : Guilford Press, 2010)
Dr. Barkley provides step-by-step strategies for managing symptoms and reducing their impact. Readers get hands-on self-assessment tools and skills-building exercises, plus clear answers to frequently asked questions about medications and other treatments. --from publisher description.
1. To get started, get evaluated : Is it possible that you have ADHD? ; Can you handle the problem on your own? ; Where can you go to get help? ; What do you need for the evaluation? ; What will the evaluation tell you? -- 2. Change your mindset: Know and own your ADHD : Know your ADHD ; Resisting impulses: the first step in self-control ; Self-control: how to get what you want ; Executive functions: the abilities that make up self control, and more ; The nature of ADHD and how you can master it ; Own your ADHD -- 3. Change your brain: medications for mastering ADHD : Why it makes sense to try medication ; The stimulants ; The nonstimulants ; What to expect from treatment -- 4. Change your life: everyday rules for success : Rule 1: Stop the action! ; Rule 2: See the past, and then the future ; Rule 3: Say the past, and then the future ; Rule 4: Externalize key information ; Rule 5: Feel the future ; Rule 6: Break it down, and make it matter ; Rule 7: Make problems external, physical, and manual ; Rule 8: Have a sense of humor! -- 5. Change your situation: mastering ADHD in specific areas of your life : Education ; Work ; Money ; Relationships ; Driving, health, and lifestyle risks ; Other mental and emotional problems ; Drugs and crime -- Appendix: A closer look at ADHD symptoms.
Includes bibliographical references and index.
Keywords: Attention-deficit disorder in adults -- Popular works; MEDICAL -- Mental Health; MEDICAL -- Psychiatry; PSYCHOLOGY -- Psychopathology -- Attention-Deficit Disorder (ADD-ADHD); PSYCHOLOGY -- Psychotherapy -- Counseling; SELF-HELP -- Personal Growth; Attention-deficit disorder in adults; Popular works